Radiation-Induced Meningiomas: A perspective from the West of Scotland. (12th October 2019) - Roberts, Mari; McIlwraith, Andrew; Owusu-Agyemang, Kevin; Hamdan, Alhafidz; Champeaux, Charles; Houston, Deborah; Grivas, Athanasios
Abstract: Introduction: Meningioma is the most common intracranial neoplasm to be induced by ionising radiation. Patients receiving childhood radiotherapy do not have routine surveillance to assess for this delayed complication. We aimed to examine our 30 year cohort of surgically treated meningioma in Glasgow. Method: We retrospectively reviewed all patients who underwent surgery for meningioma and identified those who previously had childhood cranial irradiation. We then studied their demographics including gender and age at index cranial irradiation, latency period, histological grade and outcome. Results: In total there were 982 patients with meningioma (WHO Grade 1 – 69%, Grade 2- 26%, and Grade 3- 1%). Of these, 22 patients had a radiation-induced meningioma. Eleven (50%) of these were WHO Grade 1. Median age at diagnosis of meningioma was 38 years old. Most cases were females (15; 68%, and most common indication for childhood irradiation was leukaemia (11; 50%), followed by pineal region tumours (4; 18%). Mean latency from irradiation to meningioma diagnosis was 25 years. Seven (32%) patients had multiple meningiomata; 5 (71.4%) of these had >2 lesions. Eight patients (36%) had recurrent meningiomata. Conclusion: Patients receiving cranial radiation should be enrolled into a surveillance program guided by the reported latency period. A local registry of such patients would provide more information on protective and prognostic factors.